EFEKTIVITAS SISTEM PREMI POTONG BUAH TERHADAP BIAYA PANEN PADA KEGIATAN PEMANENAN BUAH KELAPA SAWIT DI PT. SERIKAT PUTRA PERKEBUNAN LUBUK RAJA RIAU - Ni Made Suyastiri YP; Vandrias Dewantoro (Jurnal Dinamika Sosial Ekonomi, 2007)
The purposes of this research are to identify the influence of usage of Crosscut Premium System of Oil Palm to reduction crop expense, and also to know Effectiveness usage of Crosscut Premium system of oil Palm at Lubuk Raja Plantation. The research was conducted by disciptive method and for the detemination of research location use purposive method. Intake sample using the purposive sampling. To Analyze of Crosscut Premium system oil palm have an effect to reduction of crop expense used abbreviation analyze simple regression while to analyze usage of crosscut premium system of oil palm have used effective of abbreviation analyze simple regression. The result of this research indicate that decreasing cost harvest 96, 7% influenced by Crosscut Premium oil palm. While many output (TBS) which yielded 99,9% influenced by Crosscut Premium  of crop expense and palm oil, and relation of each variable is very close. From result of this research show that crosscut premium system of oil palm is very benefical for the labour and oil palm plantation itself. System premium of crosscut oil palm is very effective for increasing out and decreasing cost harvest at cropping of oil palm.Keywords : Effectiveness, premium System, Expense of crop, oil palm